Microstructural simulations of debonding, nucleation, and crack propagation in an HMX-MDB propellant - Yufei Hou; Jinsheng Xu; Changsheng Zhou; Xiong Chen (Materials & Design, 2021)
The modeling of the deformation and failure process of a cyclotetramethylene tetranitramine modified double-base (HMX-MDB) propellant based on the microstructure is of great importance for its manufacturing process and storage lifetime. In the present work, the debonding, nucleation, and crack propagation in an HMX-MDB propellant were investigated experimentally and numerically. Stress-strain responses and viscoelastic parameters were obtained through uniaxial tensile tests on the HMX-MDB propellant and stress relaxation tests on a nitrocellulose-nitroglycerine (NC-NG) propellant, respectively. A two-dimensional representative volume element (RVE) model was developed based on the molecular dynamics method by embedding HMX particles in the NC-NG matrix. A zero-thickness cohesive element was used to simulate the damage behavior of the matrix and the interface. A piecewise cohesive zone model (PCZM) was established to capture stress-strain responses resulted from the matrix rupture and the debonding process at the particle-matrix interface. The effects of matrix strength and interface strength on the mechanical properties of the HMX-MDB propellant were investigated by PCZM. The different ratio of matrix strength to interface strength revealed three kinds of HMX-MDB propellant’s damage patterns: matrix cracking, matrix cracking followed by particle-matrix interfacial debonding, and particle-matrix interfacial debonding followed by matrix cracking.